2008
DOI: 10.1037/0893-164x.22.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Links between casino proximity and gambling participation, expenditure, and pathology.

Abstract: Two studies investigated the relationship between casino proximity and gambling participation, expenditure, and pathology. In Study 1, 8,842 participants were categorized into 1 of 4 driving distances from their home to the nearest casino in the province of Quebec: 0-100 km, 100.01-200 km, 200.01-300 km, or 300.01-981 km. In Study 2, 5,158 participants, who lived within a 100-km driving distance from the Montreal casino, were classified into 1 of 5 equidistant, 20-km driving distances. A survey company intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…It is likely that some of the pathways in which the larger religious context influence individual gambling behaviors include controlling or reducing opportunities to engage in legally sanctioned gaming acts, such as lotteries and casinos (although the opportunity to gamble has changed dramatically in the past given the aforementioned information regarding the almost ubiquitous opportunities to gamble via lotteries, not to mention the growth of Internet gambling). Prior research has demonstrated that proximity to casinos and other legitimate gaming opportunities is associated with problem gambling (French, Maclean, and Ettner 2008; Welte et al 2004, 2007; see also Sevigny et al 2008, who find an inverse association between casino proximity and gambling problems) 16 . Further research is needed that can consider the association between county‐level religious participation and legal opportunities to gamble (especially casino proximity) when evaluating the role of context in predicting individual gambling acts.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that some of the pathways in which the larger religious context influence individual gambling behaviors include controlling or reducing opportunities to engage in legally sanctioned gaming acts, such as lotteries and casinos (although the opportunity to gamble has changed dramatically in the past given the aforementioned information regarding the almost ubiquitous opportunities to gamble via lotteries, not to mention the growth of Internet gambling). Prior research has demonstrated that proximity to casinos and other legitimate gaming opportunities is associated with problem gambling (French, Maclean, and Ettner 2008; Welte et al 2004, 2007; see also Sevigny et al 2008, who find an inverse association between casino proximity and gambling problems) 16 . Further research is needed that can consider the association between county‐level religious participation and legal opportunities to gamble (especially casino proximity) when evaluating the role of context in predicting individual gambling acts.…”
Section: Discussionmentioning
confidence: 99%
“…It would be desirable to have at least one item gauging the frequency of each of several types of gambling, for example, cards, lotteries, online gambling, parimutuel betting). In addition, although opportunities for gambling have proliferated due to state lotteries and various forms of online betting, some studies demonstrate that access to nearby casinos, racetracks, and other such sites may allow individuals to gamble on a more regular basis, perhaps increasing the risk of problem gambling (e.g., Welte et al 2004; but see Sevigny et al 2008). Thus, it would be helpful to know more about individual respondents' proximity to these types of facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies, but not all, have found positive results for the relationship between distance from a casino and the likelihood of problem gambling. In a Quebec study, Sevigny et al (2008) found a positive relationship between distance from a casino and gambling participation, but failed to find a relationship with problem gambling.…”
Section: Introductionmentioning
confidence: 93%